A Review of DNA Viral Infections in Psittacine Birds - KATOH, Hiroshi; OGAWA, Hirohito; OHYA, Kenji; FUKUSHI, Hideto (Journal of Veterinary Medical Science, 2010)
To date, several DNA viral infections have been reported in psittacine birds. Psittacine beak and feather disease (PBFD) is characterized by symmetric feather dystrophy and loss and development of beak deformities. PBFD is caused by beak and feather virus, which belongs to the Circoviridae, and is the most important infection in psittacine birds worldwide. Avian polyomavirus infection causes acute death, abdominal distention, and feather abnormalities. Pacheco's disease (PD), which is caused by psittacid herpesvirus type 1, is an acute lethal disease without a prodrome. Psittacine adenovirus infections are described as having a clinical progression similar to PD. The clinical changes in psittacine poxvirus-infected birds include serious ocular discharge, rhinitis, and conjunctivitis, followed by the appearance of ulcerations on the medial canthi of the eyes. Internal papillomatosis of parrots (IPP) is a tumor disease characterized by progressive development of papillomas in the oral and cloacal mucosa. IPP has been suggested to caused by papillomavirus or herpesvirus. However, information about these diseases is limited. Here we review the etiology, clinical features, pathology, epidemiology, and diagnosis of these DNA viruses.